A Numerical Model of Bank Collapse and River Meandering. Issue 12 (17th June 2021) - Zhao, Kun; Lanzoni, Stefano; Gong, Zheng; Coco, Giovanni
Abstract: Meander migration results from the interaction between inner bank accretion and outer bank erosion/collapse. This interaction has been usually treated as a long‐term average of a sequence of erosion events determined by flow hydrographs. Little attention has been paid to the role that individual bank collapse events play on meander evolution. To fill this gap, we developed a numerical model of river meandering that describes explicitly bank collapse. Results show that as bend curvature increases due to meander migration and elongation, the initially scattered locations of bank collapse events converge toward the channel section where bed shear stress attains a maximum. Simulations illustrate the observed catch‐up behavior between inner and outer banks, driven by intermittent bank collapse events. Moreover, bank collapse is found to speed up short‐term meander migration and, consistent with field observations, meanders turn out to evolve toward a state characterized by constant channel width. Plain Language Summary: Meanders are one of the most ubiquitous morphological features observed in natural rivers. They consist of a series of alternating bends that, seen from above, display one of the most striking morphological patterns in nature. The migration of meandering rivers is attributed to outer bank retreat, due to erosion, and inner bank accretion, due to deposition. In this work, we propose a morphodynamic model to investigate the effects that repeated bank collapse events have on meander evolution. Our results show that the migration of meander bends can be described through a catch‐up behavior, driven by outer bank collapse and subsequent inner bank accretion, that on average ensures a nearly constant channel width. Key Points: Meander bend migration is described through a catch‐up behavior, driven by intermittent bank collapse events As the river bend evolves increasing its apex curvature, bank collapse tends to occur at the location of maximum shear stress Individual bank collapse events speed up the short‐term migration rate of meandering rivers